Agricultural Development Council Inc : report for 1973 - Agricultural Development Council (New York: Agricultural Development Council, 1973)
This publication is a the 1973 report of the Agricultural Development Council. The Council on Economic and cultural affairs Inc. was founded by John D. Rockeffer 3rd for the charitable, scientific, and educational purpose and are designed to stimulate and support economic and related activities important to human welfare. The council supports teaching and research related to the economic and human problems of agricultural development.
lje 10/5/2017
Loans
Keywords: Agriculture---Economic aspects; Agricultural development